Sinus Floor Cortication: Classification and Prevalence. (29th June 2016) - Choucroun, Guillaume; Mourlaas, Julien; Kamar Affendi, Nur Hafizah; Froum, Stuart J; Cho, Sang‐Choon
Abstract: Purpose: To present a classification and assess the presence and degree of cortication of the sinus floor utilizing Computerized Tomography (CT) scan images. Materials and Methods: One hundred CT scans, of patient who required a sinus augmentation procedure (SAP), were evaluated and classified according to the Type of sinus floor cortication (SFC). Type 1: sinus floor showing similar or higher density than the surrounding cortical areas. Type 2: sinus floor showing less density than the surrounding cortical areas. Type 3: sinus floor showing no cortical bone. Type 4: sinus floor showing the fusion of sinus floor bone and native crestal bone. Results: The SFC were present in 31, 41, 18, and 10 cases in Type 1, 2, 3, and 4, respectively. Conclusions: This classification based on the level of cortication of the sinus floor is clinically useful as a method of determining if the dental implant can be placed simultaneously or not with the SAP, or can be placed even without a SAP.